Effect of Inhalation Aromatherapy on Pain, Anxiety, Comfort, and Cortisol Levels During Trigger Point Injection. Issue 1 (January 2020) - Kasar, Kadriye Sayin; Yildirim, Yasemin; Senuzun Aykar, Fisun; Uyar, Meltem; Sagin, Ferhan Girgin; Atay, Sevcan
Abstract : The objective of this study was to examine the effects of inhaler aromatherapy on the level of pain, comfort, anxiety, and cortisol during trigger point injection in individuals with myofascial pain syndrome. Lavender oil inhalation was found to reduce pain and anxiety during trigger point injection and to improve patient comfort, but it did not affect the saliva cortisol level.